Clinical outcomes of patients with unsuccessful mechanical thrombectomy versus best medical management of medium vessel occlusion stroke in the middle cerebral artery territory - Faizy, Tobias D.; Möhlenbruch, Markus Alfred (Journal of neuroInterventional surgery, 2025)
Background Current randomized controlled trials are investigating the efficacy and safety of mechanical thrombectomy (MT) in patients with medium vessel occlusion (MeVO) stroke. Whether best medical management (MM) is more efficient than unsuccessful vessel recanalization during MT remains unknown. - Methods This was a retrospective cohort study using data from 37 academic centers across North America, Asia, and Europe between September 2017 and July 2021. Only patients with occlusion of the distal branches (M2 and M3) of the middle cerebral artery territory were included. Unsuccessful MT was defined as a modified Thrombolysis in Cerebral Infarction score of 0-2a. Propensity score matching was used to control for confounders. The primary outcome was functional independence, defined as a modified Rankin Scale (mRS) score of 0-2 at 90 days after treatment. Multivariable regression analysis was used to assess factors associated with the primary outcome. - Results Of 2903 patients screened for eligibility, 532 patients were analyzed (266 per group) after propensity score matching. The MM group had superior functional outcomes, with 32% achieving mRS 0-1 at 90 days compared with 21% in the MT group (P=0.011). Patients in the MM group also had significantly lower rates of symptomatic intracranial hemorrhage (sICH) (3.4% vs 16%, P<0.001) and any hemorrhage (18% vs 48%, P<0.001). On multivariable regression, unsuccessful MT was associated with reduced odds of functional independence (OR 0.50, 95% CI 0.29 to 0.85, P=0.011) and increased odds of sICH (OR 4.32, 95% CI 1.84 to 10.10, P<0.001). Mortality rates were similar between groups (27% in MM vs 29% in MT, P=0.73). - Conclusion Unsuccessful MT for MeVO was linked to worse outcomes than best MM. These findings highlight the risks of prolonged attempts and emphasize the importance of efficient procedural decision-making to reduce complications and improve patient outcomes.
Veröffentlicht online: 23. Januar 2025
Gesehen am 06.10.2025